DIFFERENT DYINGS: LIVING AND DYING WITH CANCER, ORGAN FAILURE AND PHYSICAL FRAILTY. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Kendall, Marilyn; Carduff, Emma; Lloyd, Anna; Kimbell, Barbara; Cavers, Debbie; Buckingham, Susan; Boyd, Kirsty; Grant, Liz; Worth, Allison; Pinnock, Hillary; Sheikh, Aziz; Murray, Scott A.
Abstract : Background: Recent controversy around the Liverpool Care Pathway has highlighted the need to listen to patient and carer perspectives. Better understanding of how different patient groups perceive their deteriorating health and approaching death can inform palliative care developments for all conditions. Aim: To establish whether there are typical narratives of living with and dying from a variety of progressive conditions, that might provide insights into how best to provide effective, patient-centred care. Methods: We used a narrative framework to synthesise eight methodologically comparable, longitudinal, interview studies undertaken by our research group. We examined the narratives of people dying from cancer (lung, glioma and colorectal cancer), organ failure (heart, liver and chronic obstructive pulmonary disease) and physical frailty, in socioeconomically and racially diverse populations in Scotland. Results: The dataset comprised 828 in-depth interviews with 156 patients, 114 family caregivers and 170 health professionals. The cancer narratives typically had a clear beginning, middle and anticipated end. They gave a well-rehearsed account of the illness, with the dual themes of hope for recovery alongside fear of dying. In contrast, people with organ failure struggled to pinpoint when their illness began, or see meaningful patterns between acute events. Fewer spoke about death, hoping instead to avoid further deterioration. Some attributed their poor health to 'old age', others struggled to identify any specific illness. Frail older people were frustrated by their progressive loss of independence, fearing dementia or nursing home admission more than dying. Conclusions: The typical cancer narrative is very different from those in frailty or organ failure. Palliative care as a concept may be too inextricably linked to imminent death to be acceptable and appropriate for these patients. We must diversify palliative care provision to meet the range of holistic needs of all patients approaching the end of life.